Are Credit Default Swaps Spreads High in Emerging Markets : An Alternative Methodology for Proxying Recovery Value - Singh, Manmohan (Washington, D.C. : International Monetary Fund, 2003)
In times of distress when a country loses access to markets, there is evidence that credit default swap (CDS) spreads are a leading indicator for sovereign risk than the EMBI+ sub-index for the country. However, it is not easy to discern the variables that determine the level of CDS spreads in Emerging Markets (EM); traders only quote the CDS spreads and not the inputs that are required to calculate such spreads. This note provides some evidence from Argentina and Brazil that reveals inconsistency between theory and practice in pricing CDS spreads in EM. This note suggests an alternate methodology that links CTD (cheapest-to-deliver) bonds to recovery values assumed in CDS contracts. Furthermore, special features that pertain to CDS contracts (repo specialness, short squeezes by central banks) may also magnify the financial distress of a sovereign.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CDS Contract; CDS Market; CDS Spread; Recovery Value; WP; Brazil